Failure of SKF 38393-A to relieve parkinsonian symptoms induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine in the marmoset. - Close, S. P. (1985)
Chronic administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced parkinsonian symptoms, predominantly bradykinesia and tremor, in marmosets. These symptoms were reduced by L-DOPA plus benserazide but the putative D1-receptor agonist SKF 38393-A did not affect tremor and increased the bradykinesia. Neither treatment affected behaviour in normal marmosets. It is suggested that D1-receptor agonists are unlikely to be effective in the treatment of Parkinson's disease.